Tantangan dan Solusi Pendidikan Keperawatan pada Masa Pandemi Covid 19 di Indonesia (Tinjauan Literatur) - Ade Suryaman; Ismail Fahmi; Amelia Ganefianty (FORIKES, 2021)
COVID-19 is still a pandemic health problem around the world. Many sectors have been affected by the COVID-19, including the nursing education sector. Social distancing policy by the government make nursing education administrators have to change learning methods. On the other hand, education administrators are required to be able to produce quality nurse graduates, even with online learning methods. This article is a literature review that aims to analyze the impact of COVID-19 on nursing education and solutions in dealing with it. We usd article search sources in the Pubmed database with the inclusion criteria for articles from 2020 to 2021 and provide full-text. The keywords used were